Comparative Study of Pulmonary and Extra-Pulmonary Tuberculosis in Bhutan (2015-2017) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2019)
Introduction: Extrapulmonary Tuberculosis (EPTB) has been increasingly diagnosed and reported compared to Pulmonary TB (PTB) in Bhutan in the recent years. In this comparative study, our study describes the epidemiology, diagnostic modalities used, inconsistency in case-classification and treatment outcomes of PTB and EPTB cases diagnosed from 2015-2017.Methods: A retrospective descriptive study was conducted by retrieving patient records maintained at the 11 TB Reporting Centres. Using two stage cluster sampling technique, nine primary sampling units (9-PSUs) were generated for the years 2015, 2016 and 2017 respectively. Based on the highest caseloads among 32 TB Reporting Centres, nine primary clusters were selected first and final sample of 350 for each year were drawn using systematic random sampling technique from the PSUs.Results: We recruited a total of 1048 cases (PTB=555, EPTB=493) in the final descriptive analysis. The median age of the subjects was 27 years (range 1-87) with slight female predominance (53%). Students were the highest (23.85%) followed by farmers (17.94%). The proportion of PTB was (52.95%), EPTB of (47.08%) and clinically diagnosed EPTB accounted for (92%), which is extremely high. Twelve miliary/disseminated TB cases (1.15%) were miss-classified as EPTB and (56%) EPTB cases were not classified based on the body sites involved. The overall treatment success rate (TSR) of PTB and EPTB was (93.26%).Conclusion: We recommend an expert team to revisit National TB treatment guidelines on diagnosis of EPTB and ensure EPTB site/s are properly identified and documented. Sensitize clinicians and other units (ENT, Surgery, Orthopedics, MCH, General OPD etc.) on the referral of EPTB cases to Medical Specialist/Chest Physician for consultation.